2018
DOI: 10.1038/s41598-018-32237-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of differentially expressed genes and miRNAs predicts complex T3-mediated protective circuits in a rat model of cardiac ischemia reperfusion

Abstract: Thyroid hormone (T3) dyshomeostasis in the cardiac ischemia-reperfusion (IR) setting negatively impacts on mitochondria function and extracellular matrix remodeling. The modulation of cardiac miRNAs may represent the underlying molecular mechanisms, but a systems biology perspective investigating this critical issue in depth is still lacking. A rat model of myocardial IR, with or without an early short-term T3-replacement, was used to predict putative T3-dependent miRNA-gene interactions targeted to mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 50 publications
3
43
0
Order By: Relevance
“…The experimental design included an in vivo exploratory investigation on established rat models of hyperthyroidism and acute myocardial ischemia and reperfusion (IR), followed by an in vitro validation study on neonatal rat cardiomyocytes (NRCM). The left ventricle samples used in the in vivo study were collected during previous works [ 16 , 17 , 18 ]. NRCM were obtained from rat pups as described below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental design included an in vivo exploratory investigation on established rat models of hyperthyroidism and acute myocardial ischemia and reperfusion (IR), followed by an in vitro validation study on neonatal rat cardiomyocytes (NRCM). The left ventricle samples used in the in vivo study were collected during previous works [ 16 , 17 , 18 ]. NRCM were obtained from rat pups as described below.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experimental procedure, the left ventricle was immediately frozen. Myocardial ischemia/reperfusion (IR) was induced in 2–3-month-old Wistar rats by 30 min ischemia followed by unrestrained reperfusion for 3 d or 14 d. Following IR after 24 h, rats showing a low T3 state were randomly allocated to receive 48 h infusion of saline (IR group) or T3 at the replacement dose of 3 μg/kg/die (IRT3 group) [ 17 , 18 ]. The choice of infusing T3 instead of T4 was dictated by the notion that under condition of low T3 syndrome the tissue local modulation of the activity of different isoforms of deiodinases seems to favor the conversion of T4 into rT3 (metabolically inactive form) rather than T3 (metabolically active form) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, the thyroid hormones play a significant role in regulating multiple components of the MQC by improving mitochondrial biogenetics and maintaining cell function. In this regard, recent studies have indicated that T3 is involved in the mitochondrial biogenesis and protein import and provides protection in ischemic heart disease 38,39 . In the model of ischemia reperfusion (IR), low T3 impacts negatively on the mitochondrial function and also has a negative effect on the extracellular matrix remodelling 38,39 .…”
Section: Cardiometabolic Effects Of Subclinical Hypothyroidismmentioning
confidence: 99%
“…In this regard, recent studies have indicated that T3 is involved in the mitochondrial biogenesis and protein import and provides protection in ischemic heart disease 38,39 . In the model of ischemia reperfusion (IR), low T3 impacts negatively on the mitochondrial function and also has a negative effect on the extracellular matrix remodelling 38,39 . With respect to HF in patients with SCH, studies have shown that the myocardium is very sensitive to thyroid hormones and any disturbance in the circulating hormone levels can lead to HF secondary to decreased cardiac output from the systolic and diastolic myocardial dysfunction 40 .…”
Section: Cardiometabolic Effects Of Subclinical Hypothyroidismmentioning
confidence: 99%